Vancomycin Resistant Enterococci Prevalence, Antibiotic Susceptibility Patterns and Colonization Risk Factors Among HIV-Positive Patients in Health-Care Facilities in Debre Berhan Town, Ethiopia - Zike M; Ahmed AM; Hailu A; Hussien B (Infection and Drug Resistance, 2024)
Mikiyas Zike,1 Abdurahaman Mohammed Ahmed,2 Awraris Hailu,2 Bedru Hussien3 1Debre Berhan Town Health Facilities, MoH, Debre Berhan, Amhara National Regional State, Ethiopia; 2Department of Epidemiology, Debre Berhan University, Debre Berhan, Amhara National Regional State, Ethiopia; 3Department of Public Health, Madda Walabu University, Goba, Oromia National Regional State, EthiopiaCorrespondence: Bedru Hussien, Department of Public Health, Madda Walabu University, P.O. Box 302, Goba, Oromia National Regional State, Ethiopia, Tel +251911997287, Email bedru1964@gmail.comBackground: The majority of multidrug-resistant organisms found in immunocompromised patients are enterococci. The rise of vancomycin-resistant enterococci (VRE) poses a significant threat to public health. There is a scarcity of information regarding the prevalence of VRE in Ethiopia.Purpose: This study aims to determine the prevalence of VRE in fecal samples from Human Immunodeficiency Virus (HIV)-positive individuals, to identify associated factors, and to assess their susceptibility to selected commonly prescribed medications.Patients and Methods: A cross-sectional study was conducted from April 1 to July 15, 2023, on 170 HIV-positive clients at Debre Berhan Town. A pre-tested structured questionnaire was used to collect socio-demographic and clinical data. Stool sample was collected by trained health workers, and processed by standard microbiological techniques. Kirby-Bauer disk diffusion method was used for antimicrobial susceptibility testing. Data entry and analysis was carried out by SPSS Version 25. Bivariate and multivariate logistic regressions were used to assess the associated factors. Variables with a p-value of < 0.05 were considered to be significantly associated with the outcome variables and the results were displayed with tables.Results: From the total of 170 study participants, colonization of Enterococcus species was observed among 95 (55.9%). Vancomycin resistance was found in 13 (13.8%) of them with 95% confidence interval (CI) 7.4– 22.1. History of hospitalization Adjusted Odds Ratio (AOR): 11.9 (95% CI 1.11– 127.53); habit of eating uncooked food (AOR: 15.34 (95% CI 2.36– 99.63)) and invasive procedures (AOR: 23.07 (95% CI 3.54– 150)) were among the predictors of VRE. MDR (multidrug resistance) was observed in 83 (87.4%) of the isolates. The highest rate of resistance was observed for ampicillin with 72 (74.6%).Conclusion: Vancomycin and multidrug resistance of enterococci among HIV patients are significant in ART clinics of Debre Berhan Town. These warrant applicable infection prevention guidelines in the health facilities and health education on food hygiene.Keywords: Enterococci, vancomycin resistant, HIV patients, Ethiopia